MOF-based controlled-release patches for nitric oxide: fabrication, gas release profile, and preservation efficacy on cherry tomatoes - Mengting Zhao; Yingxue Tang; Xiaoyu Yin; Majida AL-Wraikat; Junfeng Fan; Xiangning Chen; Bolin Zhang (Food Chemistry, 2026)

Carbon capture technology enabled ClO₂ controlled-release active patch: Gel system construction, physicochemical characteristics, and blueberry preservation - Xiaoyu Fan; Mengru Yu; Yingxue Tang; Mengting Zhao; Xinyu Li; Junfeng Fan; Xiangning Chen; Bolin Zhang (Food Packaging and Shelf Life, 2026)

Selectively encapsulated and dry-fabricated sandwich-type patch: CO2/ClO2 differentiated dual-gas release for multi-dimensional preservation of purple cabbage - Yingxue Tang; Mengting Zhao; Mengru Yu; Xiaoyu Fan; Majida AL-Wraikat; Junfeng Fan; Xiangning Chen; Bolin Zhang (Food Chemistry, 2026)

Preparation of Lycium barbarum oligosaccharides using microwave-assisted FeCl3-DES system: Efficacy, physicochemical characteristics, and probiotic effects - Shuchang Guo; Mengru Yu; Peiyao Zhang; Xiaoya Wang; Jiawei Xue; Yuxin Liu; Xiaoyu Yin; Lu Lu; Junfeng Fan; Yamei Yan; Bolin Zhang; Bo Zhang (Food Chemistry, 2026)

Safety evaluation of pasteurized Akkermansia muciniphila YGMCC2645 - Jie Tian; Zhili He; Minlei Zhao; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Ying Xia; Shaohua Fu; Wenxiang Yang; Lanjie Pei; Jun Fan; Jianguo Chen; et al. (Food and Chemical Toxicology, 2026)

A large-scale framework for deriving tidal flat topography from SWOT data - Hao Xu; Nan Xu; Wenyu Li; Kai Tan; Chunpeng Chen; Huan Li; Lucheng Zhan; Pei Xin; Jiaqi Yao; Peng Li; Zhen Zhang; Haipeng Zhao; et al. (Remote Sensing of Environment, 2026)

Multi-Scale Pore System and Its Implication for Shale Oil Occurrence in Alkaline Lacustrine Mixed Sedimentary Shale Reservoirs: A Case Study from Fengcheng Formation, Mahu Sag, Junggar Basin - Yuanhao Zhang; Zhenxue Jiang; Jiaqi Chang; Zhiye Gao; Liliang Huang; Wenjun He; Chengju Zhang; Lei Chen; Qingqing Fan; Yunhao Han; Bolin Zhang; Chao Chen (Journal of Earth Science, 2026)

Mechanisms for initiation and termination of extraordinarily high total organic carbon in the Longmaxi Formation, Yangtze Platform, South China - Zongyuan Sun; Hao Chen; Xianguo Lang; Bolin Zhang; Qing Chen; Kun Zhao; Shengxian Zhu; Fangqi Zhao; Feng Liang; Chuyuan Liu; Junxuan Fan (Marine and Petroleum Geology, 2025)

Occurrence of Maillard reaction products during green extraction of Lycium barbarum polysaccharides using deep eutectic solvents - Mengru Yu; Rubi Zhang; Xiaoyu Yin; Peiyao Zhang; Zilan Zhai; Lu Lu; Junfeng Fan; Yamei Yan; Bolin Zhang; Bo Zhang (Food Chemistry, 2025)

Sodium iron chlorophyllin-reinforced chitosan/gelatin films for fresh-cut vegetable packaging - Bing Yan; Jingyu Huang; Xiaoyu Yin; Xinyue Guan; Yingxue Tang; Jiamin Wen; Bolin Zhang; Junfeng Fan; Xiuting Li (Food Packaging and Shelf Life, 2025)

Fabric/hydrogel sandwich-structured flexible sensor with broad sensing range for pressure and temperature sensing - BoLin Fan; XinYi Tian; ShiLong Dong; HongWei Tian; Bao Shi; RuoSi Yan; YaJun Zhang; XuDong Yu (Chemical Engineering Journal, 2025)

Safety evaluation of Nannochloropsis gaditana oil as a novel food - Jingjing Qu; Taiping Zhu; Xiaoya Du; Yingjing Zhang; Jie Tian; Ying Xia; Xianghong Ke; Shaohua Fu; Bolin Fan (Regulatory Toxicology and Pharmacology, 2025)

Preparation of oat metal ion chelating peptides via froth floatation: Efficacy, molecular characteristics, and their anti-browning effects - Xinyue Guan; Xixi Gao; Xiaoyu Yin; Nan Zhang; Bing Yan; Jingyu Huang; Xiangning Chen; Junfeng Fan; Xiuting Li; Bolin Zhang (Food Chemistry, 2025)

Coupled dynamic modeling and analysis for collecting asteroid soil using a flexible brush sampler - Qichen Sun; Bolin Zhang; Bo Lei; Fan Guo; Jianfeng Man; Jinyang Liu; Zeng Zhao (Advances in Space Research, 2025)

A novel hybrid machine learning approach for accurate retrieval of ocean surface chlorophyll-a across oligotrophic to eutrophic waters - Ting Qin; Tianlong Liang; Donglin Fan; Hongchang He; Guiwen Lan; Bolin Fu (Environmental Research, 2025)

Safety evaluation of alpha-glycerylphosphorylcholine as a novel food - Jie Tian; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Shaohua Fu; Ying Xia; Wenxiang Yang; Yanhua Zeng; Jun Fan; Yanmei Li; Bolin Fan (Food and Chemical Toxicology, 2025)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

Effect of rehabilitation exercise on locomotion performance of captive Bengal slow loris - Xing Bolin; Liao Linhong; Han Dongchen; Liu Jiayong; Zhao Kairui; Fan Yumai; Teng Ping; Zhang Yan; Huang Anqi; Zeng Changjun; Xie Meng; Ni Qingyong (Applied Animal Behaviour Science, 2024)

A high-resolution record of the late Hirnantian to Aeronian marine redox change in South China and its relationship with the record of graptolite biodiversity - Zongyuan Sun; Fangqi Zhao; Michael J. Melchin; Junxuan Fan; Bolin Zhang; Xin Jin; Zihu Zhang; Shengchao Yang; Qing Chen; Yiying Deng; Linna Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Genetic and prenatal developmental evaluation of anthraquinone - Jingjing Qu; Yinjing Zhang; Chunxia Liu; Qianqian Xie; Tong Ou; Bolin Fan; Yan Song (Toxicology Letters, 2023)

Metal coordinating-induced self-assembly of cyclic lipopeptides into high-performance antimicrobial supramolecules - Jinglin Ding; Shufan Zeng; Yueqing Wang; Xiaoyu Yin; Bo Zhang; Bolin Zhang; Shandong Xu; Yanyan Zhang; Jiangfu Zheng; Junfeng Fan; Mengze Wang (Food Chemistry, 2023)

Extended one generation reproductive toxicity study and effect on gut flora of genetically modified rice rich in β-carotene in wistar rats - Ying Xia; Shanshan Zuo; Yanhua Zheng; Wenxiang Yang; Xiaoqiao Tang; Xianghong Ke; Qin Zhuo; Xiaoguang Yang; Yang Li; Haiyi Liu; Bolin Fan (Reproductive Toxicology, 2023)

SERS determination of hydroxy-α-sanshool in spicy hotpot seasoning: The strategy to restrain the interference of capsaicin and its mechanism - Di Zhang; Yushan Fan; Xiaoxia Sun; Xiaoou Wei; Zitao Lin; Xinai Zhang; Jiyong Shi; Maurizio Battino; Yunyun Gong; Bolin Shi; Xiaobo Zou (Food Chemistry, 2023)

Effects of traditional and advanced drying techniques on the physicochemical properties of Lycium barbarum L. polysaccharides and the formation of Maillard reaction products in its dried berries - Xiaomin Tang; Yaqiong Zhang; Feiyang Li; Na Zhang; Xiaoyu Yin; Bo Zhang; Bolin Zhang; Wenrui Ni; Mengze Wang; Junfeng Fan (Food Chemistry, 2023)

A new cavitation model for simulating steady and unsteady cavitating flows - Jie He; Changjun Li; Wenlong Jia; Bolin Qiu; Fan Yang; Caigong Zhang (Ocean Engineering, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

The interfacial destabilization of bile salt-emulsified oil droplets, essential for lipase function, is mediated by Lycium barbarum L. leaf polysaccharides - Na Zhang; Xue Han; Rumeng Yu; Xiaomin Tang; Bo Zhang; Yanyan Zhang; Xiaoyu Yin; Wenrui Ni; Mengze Wang; Bolin Zhang; Junfeng Fan (Food Hydrocolloids, 2023)

Synergistic multi-altimeter for estimating water level in the coastal zone of Beibu Gulf using SEL, ALES + and BFAST algorithms - Jiaoling Qin; Sunzhe Li; Hang Yao; Bolin Fu; Hongchang He; Feng Wang; Lilong Liu; Donglin Fan; Xu He; Yuyang Li (Frontiers in Marine Science, 2023)
Accurately monitoring and predicting the large-scale dynamic changes of water levels in coastal zones is essential for its protection, restoration and sustainable development. However, there has been a challenge for achieving this goal using a single radar altimeter and retracking technique due to the diversity and complexity of coastal waveforms. To solve this issue, we proposed an approach of estimating water level of the coastal zone in Beibu Gulf, China, by combination of waveform classifications and multiple sub-waveform retrackers. This paper stacked Random Forest (RF), XGBoost and CatBoost algorithms for building an ensemble learning (SEL) model to classify coastal waveforms, and further evaluated the performance of three retracking strategies in refining waveforms using Cryosat-2, SARAL, Sentinel-3 altimeters. We compared the estimation accuracy of the coastal water levels between the single altimeter and synergistic multi-altimeter, and combined Breaks for Additive Season and Trend (BFAST), Mann-Kendall mutation test (MK) with Long Short-Term Memory (LSTM) algorithms to track the historical change process of coastal water levels, and predict its future development trend. This paper found that: (1) The SEL algorithm achieved high-precision classification of different coastal waveforms with an average accuracy of 0.959, which outperformed three single machine learning algorithms. (2) Combination of Threshold Retracker and ALES+ Retracker (TR_ALES+) achieved the better retracking quality with an improvement of correlation coefficient (R, 0.089~0.475) and root mean square error (RMSE, 0.008∼ 0.029 m) when comparing to the Threshold Retracker & Primary Peak COG Retracker and Threshold Retracker & Primary Peak Threshold Retracker. (3) The coastal water levels of Cryosat-2, SARAL, Sentinel-3 and multi-altimeter were in good agreement (R>0.66, RMSE<0.135m) with Copernicus Climate Change Service (C3S) water level. (4) The coastal water levels of the Beibu Gulf displayed a slowly rising trend from 2011 to 2021 with an average annual growth rate of 8mm/a, its lowest water level focused on May-August, the peak of water level was in October-November, and the average annual growth rate of water level from 2022-2031 was about 0.6mm/a. These results can provide guidance for scientific monitoring and sustainable management of coastal zones.

CHLNET: A novel hybrid 1D CNN-SVR algorithm for estimating ocean surface chlorophyll-a - Donglin Fan; Hongchang He; Ruisheng Wang; You Zeng; Bolin Fu; Yuankang Xiong; Lilong Liu; Yong Xu; Ertao Gao (Frontiers in Marine Science, 2022)
Developing a unified chlorophyll-a (Chla) inversion algorithm for cross-water types is a significant challenge owing to the insufficiency of input features and training samples. Although machine learning algorithms can build a consistent model for different trophic waters, the accuracy of the inversion is dependent on the quality of the extended features. Here, we designed a novel hybrid framework called CHLNET, which combines a one-dimensional convolutional neural network (1D CNN) and support vector regression (SVR). The 1D CNN is used to extract features from the original band features, and the SVR is used to perform a fit of Chla. CHLNET is trained and tested using match-up pairs of SeaWiFS remote sensing reflectance [Rrs(λ)] in situ with Chla ranging from 0.009 mg/m³ to 138.046 mg/m³, which covers mostly ocean water types. Performance metrics in the log space of CHLNET were better than those of the state-of-the-art algorithms on the testing dataset, and CHLNET had the best overall performance with the largest cover area in the star plot. The frequency distribution of predicted Chla by CHLNET was more consistent with that of in situ Chla. While the spatial pattern was not smooth in low Chla concentration waters, CHLNET demonstrated excellent mapping ability at the global and local scales in high Chla concentration waters. Through the band-shift method, which transfers the Rrs(λ) of MERIS and MODIS-Aqua to the Rrs(λ) of SeaWiFS in the visible spectral range, CHLNET obtained better accuracy than the blended algorithm of OCx and CI on MERIS and MODIS-Aqua matchups, which validates the generalization of CHLNET on cross-sensor types. The results indicate that CHLNET avoids the drawbacks of manually constructing extended features and the need for merging water type-appropriate algorithms for Chla retrieval, as well as provides a new idea for unified Chla concentration inversion across water types. Thus, CHLNET may serve as an alternative approach for Chla inversion.

Evaluation of LAI Estimation of Mangrove Communities Using DLR and ELR Algorithms With UAV, Hyperspectral, and SAR Images - Bolin Fu; Jun Sun; Yeqiao Wang; Wenlan Yang; Hongchang He; Lilong Liu; Liangke Huang; Donglin Fan; Ertao Gao (Frontiers in Marine Science, 2022)
The high-precision estimation of mangrove leaf area index (LAI) using a deep learning regression algorithm (DLR) always requires a large amount of training sample data. However, it is difficult for LAI field measurements to collect a sufficient amount of sample data in mangrove wetlands. To tackle this challenge, this paper proposed an approach for expanding training samples and quantitatively evaluated the performance of estimating LAI for mangrove communities using Deep Neural Networks (DNN) and Transformer algorithms. This study also explored the effects of unmanned aerial vehicle (UAV) and Sentinel-2A multispectral, orbital hyper spectral (OHS), and GF-3 SAR images on LAI estimation of different mangrove communities. Finally, this paper evaluated the LAI estimation ability of mangrove communities using ensemble learning regression (ELR) and DLR algorithms. The results showed that: (1) the UAV images achieved the better LAI estimation of different mangrove communities (R 2 = 0.5974–0.6186), and GF-3 SAR images were better for LAI estimation of Avicennia marina with high coverage (R 2 = 0.567). The optimal spectral range for estimating LAI for mangroves in the optical images was between 650–680 nm. (2) The ELR model outperformed single base model, and produced the high-accuracy LAI estimation (R 2 = 0.5266–0.713) for different mangrove communities. (3) The average accuracy (R 2 ) of the ELR model was higher by 0.0019–0.149 than the DLR models, which demonstrated that the ELR model had a better capability (R 2 = 0.5865–0.6416) in LAI estimation. The Transformer-based LAI estimation of A. marina (R 2 = 0.6355) was better than the DNN model, while the DNN model produced higher accuracy for Kandelia candel (KC) (R 2 = 0.5577). (4) With the increase in the expansion ratio of the training sample (10–50%), the LAI estimation accuracy (R 2 ) of DNN and Transformer models for different mangrove communities increased by 0.1166–0.2037 and 0.1037–0.1644, respectively. Under the same estimation accuracy, the sample enhancement method in this paper could reduce the number of filed measurements by 20–40%.

The Streptococcus agalactiae Ribose Binding Protein B (RbsB) Mediates Quorum Sensing Signal Uptake via Interaction with Autoinducer-2 Signals - Bolin Fan; Lixia Pan; Zhongliang Wang; Eakapol Wangkahart; Yuchong Huang; Dengfeng Yang; Jichang Jian; Yu Huang; Bei Wang (Journal of Ocean University of China, 2021)

Pharmacokinetics of Sodium Selenite in Rat Plasma and Tissues After Intragastric Administration - Xueying Zeng; Xiaotian Zhang; Bolin Fan; Yanmei Li; Ziming Jia; Wenyao Huang; Jiafa Liu; Gang Liu (Biological Trace Element Research, 2020)

Efficient inhibition of Cronobacter biofilms by chitooligosaccharides of specific molecular weight - Jun Lu; Qiming Chen; Bolin Pan; Zhen Qin; Liqiang Fan; Quanming Xia; Liming Zhao (World Journal of Microbiology and Biotechnology, 2019)